Premodern Confederacies: Balancing Strategic Collective Action and Local Autonomy - Birch, Jennifer (Frontiers in Political Science, 2022)
A confederacy is generally understood to be a formal, institutionalized alliance of peoples who act in mutual support to achieve common ends. While the emergence and maintenance of early and pre-modern states have received tremendous scholarly attention in the social sciences, the same cannot be said for confederations. This paper examines common features of premodern confederacies as an initial effort towards developing a body of theory aimed at exploring and explaining confederacies, leagues, and other modes of collective and regional governance. The central thesis posed is that confederation was an ongoing political process that provided a means for a diverse range of political formations to achieve collective strategic goals at a distance without sacrificing autonomy. Selected case studies ranging from Pre-Columbian North America to Medieval Europe are explored to evaluate this position. The case studies show that confederacies were capable of integrating a diverse range of political formations, from tribes to kingdoms. The question of whether or not confederacies constitute ‘good government’ is considered and since the objective of a confederacy is generally not to govern, the answer depends on the political organization of its constituent parts.